2021
DOI: 10.1021/jacs.1c06290
|View full text |Cite
|
Sign up to set email alerts
|

Red-Emissive Cell-Penetrating Polymer Dots Exhibiting Thermally Activated Delayed Fluorescence for Cellular Imaging

Abstract: Fluorescence imaging in living cells is key to understanding many biological processes, yet autofluorescence from the sample can lower sensitivity and hinder high-resolution imaging. Time-gated measurements using phosphorescent metal complexes can improve imaging, at the cost of potential toxicity from the use of heavy metals. Here, we describe orange/red-emitting polymer dots (Pdots) exhibiting thermally activated delayed fluorescence (TADF) for time-gated imaging. Inspired by the cell invasion mechanism of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 49 publications
3
67
0
Order By: Relevance
“…As aforementioned, disulfide bonds are highly tolerant to the low level of lysosomal GSH and pH conditions, which disfavor intracellular prodrug activation if P1NP enters cells via endocytosis, known as the most normal pathway for anionic nanomaterials without decoration of cell-penetrating ligands. Strong reducing agent tris­(2 carboxyethyl)­phosphine hydrochloride could be more efficient in inducing disulfide bond scission, but the poor permeability to the cell membrane limited its use. Currently, how to effectively induce cleavage of disulfide bonds of nanomaterials trapped in lysosome compartments remains a big challenge frequently ignored.…”
Section: Resultsmentioning
confidence: 99%
“…As aforementioned, disulfide bonds are highly tolerant to the low level of lysosomal GSH and pH conditions, which disfavor intracellular prodrug activation if P1NP enters cells via endocytosis, known as the most normal pathway for anionic nanomaterials without decoration of cell-penetrating ligands. Strong reducing agent tris­(2 carboxyethyl)­phosphine hydrochloride could be more efficient in inducing disulfide bond scission, but the poor permeability to the cell membrane limited its use. Currently, how to effectively induce cleavage of disulfide bonds of nanomaterials trapped in lysosome compartments remains a big challenge frequently ignored.…”
Section: Resultsmentioning
confidence: 99%
“…A Pdot is a water-dispersed nanoparticle consisting of 450% organic semiconductor polymer by weight or volume, and we and others have recently shown that nanoparticles with a guanidinium-rich corona block and TADFactive core block can quickly enter mammalian cells by acting as mimics for cation-rich cell-penetrating peptides. 19,41 Here, TADF dye-loaded nanoparticles are instead prepared by encapsulating small-molecule emitters into the nanoparticle core via self-assembly. 19,42,43 Next, dyes were encapsulated into glassy organic dots (g-Odots), formed by liquefying a small-molecule organic semiconductor in the presence of TADF dye and a surfactant at high temperature under microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Algar and Hudson's groups recently developed red-emissive TADF-grafted Pdots for time-gated cellular imaging with high contrast. 74 For NIR-II imaging, fortunately, the autofluorescence is less considered because of the significantly reduced autofluorescence in the NIR-II window.…”
Section: Introductionmentioning
confidence: 99%